Term spontaneous trial of labor in nulliparous women of short stature: A hospitals-based cohort study. (March 2020) - Boujenah, Jérémy; Carbillon, Lionel; Banh, Pauline; Sibony, Olivier; Korb, Diane
Highlights: Trial of labor is a reasonable option for short stature women (<150 cm). The high risk of medical interventions emphasize that the maternal height should be included as a criteria for the choice of place of birth. Customized gestational-related optimal weigh or the threshold of 3.5 kg could be helpful to identify LGA fetus in short maternal stature. Abstract: Objectives: To study the mode of delivery in a well selected cohort of short nulliparous women. Study design: Hospitals-based cohort study between 2010-2018. The threshold (150 cm, i.e 2, 3°p), for the short stature was chosen before the analysis by corresponding to – 2SD of the average population size distribution of all women who delivered over the same period: 2010–2018. Were included nulliparous women with a heigh ≤ 150 cm in term spontaneous labor with a single livung fetus in vertex presentation without malformation. Exclusion criteria were: multiparous, scarred uterus, twin pregnancy, induced labor, preterm delivery (< 37 W P), non-vertex pregnancy, medical termination of pregnancy, stillbirth, severe fetal malformations, pre-labor cesarean, and late dating ultrasound. The main outcome was the mode of delivery. Univariate and multivariate analysis adjusted on potential confounding variable were performed to investigate the risk of intrapartum CS. Results: 178 nulliparous women were included. The mean height was 148 cm. The rate of spontaneous vaginal delivery, operative vaginal delivery a nd intrapartum CS were :35, 4 %, 35, 4 % and 29, 2 % respectively. Intrapartum CS was performed during the first stage labor in 15 (28, 8 %) women and during the second stage in 37 (71, 2 %) women. An arrest of labor was significantly more frequent in the active labor than the early labor stage: 62, 1 % vs. 33.3 % (p = 0, 02). In univarate analysis were associated with intrapartum CS : Gestational diabetes, birthweight> 3, 5 kg, individual adjusted birthweight >90°p, occiput posterior, oxytocin use, cephalic circumference. After adjustment on birthplace and overweight (BMI over 25), only a birthweight > 3, 5 kg remains associated with the risk of intrapartum CS (aOR4.3 ;95 %CI 1.96–10.2). Conclusion: An attempt of vaginal birth is a reasonable option for short stature women. Maternal height could be included in the selection criteria for planned birth center or home birth. The customized gestational-related optimal weigh could be useful to identify large of gestational age fetus.